"Co doopravdy jest" aneb vztah teorie a praxe ve výtvarné výchově. "What really is" or the relationship between theory and practice in Art lessons. - Šobáňová Petra (Czech Pedagogical Society, 2012)
This paper reflects the current situation of educational theory and practice,and it deals in particular with art lessons which show significant disproportion between theory and educational reality in schools. In the introduction, the reasons behind the opposing conceptions of the terms theory and practice are outlined andvarious philosophical approches introduced. The relationship between theory and practice in education is influenced by the fact that theoretical constructs tend to have rather normative character with the objective to be applied and to form the practice. In terms of having strained relationship between theory and practice, art lessons are no diff erent to other educational subjects. The paper further explains the impact of fine art and its theory on art lessons, and it also presents examples of the clash between theory and practice taken from the history of the subject. Current issues which preventthe implementation of theoretical findings into practice are non-parallel existence of both fields and deficiencies in knowledge base of teaching profession, which were detected in practice among art teachers and which were related to their knowledgeof both the curriculum and functional dictionary.